VD_FINDINFO Arrêt / 2014 / 766 vom 21. Mai 2015 - VD Tribunal cantonal (2015)
DEGRÉ DE L'INCAPACITÉ DE TRAVAIL, HERNIE DISCALE, EXPERTISE, FORCE PROBANTE | 28 LAI, 4 al. 1 LAI, 16 LPGA, 6 LPGA, 7 al. 1 LPGA, 8 LPGA